2008
DOI: 10.1111/j.1365-2893.2008.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Tailored regimen of interferon alpha for HBeAg‐positive chronic hepatitis B: a prospective controlled study

Abstract: The response to interferon-alpha treatment of patients with chronic hepatitis B under the current protocol is not satisfactory. The aim of this study was to try an alternative approach to improve treatment outcome. Of 374 HBeAg-positive patients, 127 of them received 5 million units of interferon-alpha thrice weekly for 6 months and constituted the control group, while 247 in the study group received the same dosage but the duration of treatment was tailored. The study protocol provided for continuation of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…92,93 An Asian study of IFN therapy regimens lasting six to ten months identified therapeutic benefits six months after the end of therapy in 30% of cases, compared to just 7% in the control group. 94 An even longer therapy regimen of 24 months achieved sustained quiescence of hepatitis in 30% of cases and 18% HBsAg elimination after six years. 95 In light of these findings, continued administration of IFN is recommended overseas for patients with HBeAg negative chronic hepatitis B. IFN therapy has also been shown to suppress carcinogenesis and deliver improved life expectancies in HBeAg negative patients with chronic hepatitis B, as with HBeAg positive patients.…”
Section: Therapeutic Effect In Patients With Hbeag Negative Chronic Hmentioning
confidence: 97%
See 1 more Smart Citation
“…92,93 An Asian study of IFN therapy regimens lasting six to ten months identified therapeutic benefits six months after the end of therapy in 30% of cases, compared to just 7% in the control group. 94 An even longer therapy regimen of 24 months achieved sustained quiescence of hepatitis in 30% of cases and 18% HBsAg elimination after six years. 95 In light of these findings, continued administration of IFN is recommended overseas for patients with HBeAg negative chronic hepatitis B. IFN therapy has also been shown to suppress carcinogenesis and deliver improved life expectancies in HBeAg negative patients with chronic hepatitis B, as with HBeAg positive patients.…”
Section: Therapeutic Effect In Patients With Hbeag Negative Chronic Hmentioning
confidence: 97%
“…At the same time, however, subsequent increases in HBV DNA levels and recurrence of hepatitis are also common, with sustained effects in only 10%–15% of patients for four to six months of IFN therapy, and 22% for 12 months of therapy . An Asian study of IFN therapy regimens lasting six to ten months identified therapeutic benefits six months after the end of therapy in 30% of cases, compared to just 7% in the control group . An even longer therapy regimen of 24 months achieved sustained quiescence of hepatitis in 30% of cases and 18% HBsAg elimination after six years .…”
Section: Pharmacotherapy (1) – Ifnmentioning
confidence: 99%
“…A group of investigators in China have investigated the use of on-treatment HBV DNA decline to guide the treatment duration of conventional interferon in HBeAg-positive chronic hepatitis B patients 31. In the HBV DNA guided therapy group, interferon-α was continued until the HBV DNA level ceased to decrease by 1 log copies/ml at a 2-monthly interval, and these patients received a median of 10 (range 2–24) months of interferon.…”
Section: Looking Into the Future: Individualised Treatmentmentioning
confidence: 99%